Ruang Lingkup Evaluasi Pembelajaran Mata Pelajaran IPA Siswa SMP: Tinjauan Sistematis - Riska Fitriani; Lega Anatri; Okta Saputra Joint; Risnita Risnita (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This assessment provides space for students with non-academic weaknesses in science subject skills. This research was used to obtain information related to the scope of evaluation of junior high school students' natural science learning: A Systematic Review. Methodology: The review method was chosen to obtain research journals with keywords in the scope of evaluation of junior high school science learning on Google reference sources scholar, science direct, and research gates. Twenty journals were reviewed based on author (year), sample, study design, the scope of the evaluation, and findings. Main Findings: The results of the review show that the scope of learning evaluation can be carried out based on the context to be assessed, such as the scope of the cognitive domain, affective domain, and psychomotor domain. The scope of learning evaluation in the cognitive domain can be in the form of observation and understanding, the affective domain can be in the form of responses given by students as long as the teacher provides knowledge, and the psychomotor domain is in the form of a skills assessment rubric such as doing practicum after being given theory by the teacher. Novelty/Originality of this study: This research can contribute to the world of education, especially in evaluating science learning.